Feasibility of nationwide mapping of health facilities and community health workers in low-resource humanitarian contexts: lessons from Afghanistan - Boniface Francis Kalanda (International Journal Of Community Medicine And Public Health, 2026)
Background: Reliable, up-to-date data on health facilities and community health workers (CHWs) are essential for effective health system planning, particularly in fragile and humanitarian settings where information gaps are common. However, large-scale mapping exercises are often considered impractical in such contexts. Methods: In 2025, a nationwide mapping of health posts and CHWs was conducted across all provinces of Afghanistan. A total of 1,291 community health supervisors were trained and deployed using a cascading model to collect georeferenced data through digital tools. Data collected included facility functionality, CHW demographics, education levels, and training status. Results: The mapping covered 16,547 health posts and 32,849 CHWs, representing the first comprehensive CHW dataset since 2010. Findings confirmed that all health posts were operational. Approximately half of CHWs had at least a high school education. The use of digital tools improved data accuracy and timeliness, while local engagement enhanced implementation efficiency. Conclusions: Nationwide mapping of health systems is feasible even in complex humanitarian settings. Key success factors include structured training, digital data collection, and strong local ownership. These findings highlight the importance of investing in routine mapping to strengthen evidence-based planning and optimize CHW deployment.